Level of Confidence Paragliding Athletes During Competition - Cindy, Dwi Putri; Wahyudi, Heri; ,, Pudjijuniarto; Irawan, Roy Januardi (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
Self-confidence is a crucial psychological factor that supports athletic performance, especially in extreme sports like paragliding, which require high levels of mental preparedness. Paragliding athletes face challenges that test their courage, focus, and mental resilience, making confidence a key element during competitions. While many studies have examined confidence in various sports, research specifically addressing the confidence level of paragliding athletes during competition remains scarce. This study aims to describe the self-confidence level of paragliding athletes in a competitive context. A descriptive quantitative method was employed, using a Likert-scale questionnaire distributed to 50 athletes who had competed in league-level events. The research instrument was based on psychological indicators reflecting internal and external confidence factors. Results showed that 90% of athletes had high confidence, 10% had moderate confidence, and none had low confidence. The mean confidence score was 76.4, with a standard deviation of 5.894, indicating an overall optimal psychological state. In conclusion, paragliding athletes demonstrated high levels of self-confidence in competition, making it a valuable psychological asset for enhancing performance. It is recommended that coaches and sports institutions provide continuous psychological support through mental training and self-efficacy development programs.